SARS-CoV-2 spike antigen-specific B cell and antibody responses in pre-vaccination period COVID-19 convalescent males and females with or without post-covid condition - Limoges, Marc-André; Quenum, Akouavi Julite Irmine; Chowdhury, Mohammad Mobarak Hussain; Rexhepi, Fjolla; Namvarpour, Mozhdeh; Akbari, Sara Ali; Rioux-Perreault, Christine; Nandi, Madhuparna; Lucier, Jean-François; Lemaire-Paquette, Samuel; Premkumar, Lakshmanane; Durocher, Yves; et al. (Frontiers in Immunology, 2023)
Post-COVID Condition (PCC) is lingering illness that afflicts a significant proportion of COVID-19 patients from three months after clearing SARS-CoV-2 infection. Therapy for PCC is only palliative and the underlying disease mechanisms are unclear. The wide spectrum of PCC symptoms that can affect different organs and the detection of viral components in tissues distant from lungs raise the possibility that PCC may be associated with aberrant immune response due to presence of viral antigens. Therefore, we studied B cell and antibody responses to the spike and nucleoprotein antigens in PCC patients who cleared mild SARS-CoV-2 infection during the pre-vaccination COVID-19 pandemic period. We observed divergent patterns of immune reactivity to the spike protein in PCC males and females at different times post-infection, suggesting that the immune responses in PCC may also be influenced by sex-related factors.